Legal Realism Perspective on the International Court of Justice Judges in the 2023–2024 Israeli Occupation of Palestine - Ramadhani Salsabila, Nasywa; Aswar, Hasbi; Munzilin, Khairul (Department of International Relations, Hasanuddin University, 2026)
The research analyzes how legal and political factors, as well as personal considerations, influence judges' decisions at the International Court of Justice (ICJ) in the 2023-2024 South Africa v. Israel case. From a legal realist perspective, this paper analyzes the work of 15 judges of the International Court of Justice (ICJ). The study explores the potential impact of national ties, political contexts, and external interest groups on the court's temporary orders. The present study posits that extraneous power relations, interest groups, and interest-based partnerships, alongside political alliances, can influence the judicial system's administration of justice. The article's conclusion posits that, despite the ostensible autonomy of International Court of Justice (ICJ) judges, their jurisprudence in political cases often aligns with the foreign policies of their respective nations. This observation calls into question the prevailing concept of legal fairness within the framework of international law. The findings show that judges vote in line with their states’ geopolitical interests in which political alignments steer judicial reasoning.